Reduction of the Energy Demand With Passive Approaches in Multifamily Nearly Zero-Energy Buildings Under Different Climate Conditions - Elnagar, Essam; Köhler, Benjamin (Frontiers in Energy Research, 2020)
Nearly zero-energy buildings (nZEBs) will be the standard in Europe in the future. How nZEBs are defined and therefore designed varies amongst Europe due to different national definitions/ legislations. Furthermore, finding the optimal building design and technology sets for nZEBs under different boundary conditions (climate, availability of renewable energy sources on-site etc.) and for different building types (residential, non-residential) is still a challenge. Many studies in the field focus on active technologies and renewable energies in buildings. However, the effects of passive approaches on energy consumption are not quantified. This paper therefore focuses on the quantification of the effects of passive design approaches/ technologies to improve the energy performance of buildings. Passive approaches are the basis for finding optimal nZEB technology sets. Technology sets are combinations of different types of technologies in nZEBs for both the satisfaction of energy needs and thermal comfort requirements. In this paper different passive approaches for already realized buildings in different European countries with different climate conditions (Stuttgart (Germany), Kiruna (Sweden) and Palermo (Italy)) are demonstrated. Even though several technologies are available to achieve nZEBs, applying and combining these technologies in an optimal way is still a challenge. Furthermore, higher initial investment costs for nZEBs are an obstacle for the market acceleration of nZEBs. Hence finding the best trade-off amongst the different goals, optimizing the most promising passive approaches that can be applied is a central part of the solution.